Terms of specialized nursing language in the care of the newborn with central venous catheter - Prado,Nanete Caroline da Costa (2022)
ABSTRACT Objective: To construct and validate a specialized nursing terminology for the care of newborns with peripherally inserted central venous catheters (PICC), based on the Betty Neuman Systems Model. Methods: Methodological study, carried out in a public maternity hospital, operationalized by the steps: extraction of terms from medical records of neonates using PICC; normalization; cross-mapping with the 2019/2020 version of ICNP®; organization in the Seven Axes; and content validation with nurses using content validity index and kappa coefficient. Results: 1,718 terms were extracted, and 372 relevant terms were normalized, with 265 constants and 107 non-constants. A total of 335 terms were validated, 246 of which were constant and 89 were not constant, which reached an agreement index and kappa ≥ 0.80. Conclusion: Relevant terms were identified, which aid newborns using central venous catheters; thus, a terminological subset will be contributed to information in nursing practice.